How to analyze organizational crime: theory, concepts, and methods - Pohlmann, Markus (Organizational crime, 2023)
When we talk about rule violations in organizations, offenses often come up in which employees have faked invoices or implemented fraudulent plots to the detriment of the organization. In this paper, we are more interested in rule violations that were carried out for the benefit of legal organizations and according to their informal rules. Nearly half of the FCPA corruption cases in the U.S. follow this pattern of organizational crime. But how can organizational crime be theoretically classified and operationalized? How can informal rules be empirically identified and determined, and how can informality in organizations be measured? This article is devoted to answering these questions. Although organizational crime is often described in the literature, and corporate criminal laws have also been passed in many countries, the conceptual and empirical analysis of the phenomenon still leaves much to be desired. This article aims to contribute to this analysis.
Gesehen am 10.05.2023